Ovarian reserve modulates the impact of vitamin D deficiency on assisted reproductive outcomes in patients undergoing controlled ovarian hyperstimulation - He, Lina; Xu, Qing; Hao, Li; Ran, Xu; Qiu, Yamin; Lin, Jie; Chen, Wei (Frontiers in Nutrition, 2024)
Objective The association between vitamin D deficiency and ovarian reserve-specific outcomes of assisted reproductive technology (ART) remains uncertain. This study aimed to investigate the role of ovarian reserve in the association between basal serum vitamin D levels and ART outcomes in patients undergoing controlled ovarian hyperstimulation (COH). Methods A total of 1,333 infertile women undergoing COH cycles were retrospectively analyzed. Patients were divided into a vitamin D deficiency group (serum vitamin D < 20 ng/mL) and a normal vitamin D group. Univariate and multivariate logistic regression analyses were performed to estimate the relationship between vitamin D deficiency and pregnancy outcomes including biochemical pregnancy rate, clinical pregnancy rate, miscarriage rate, and live birth rate in the overall cohort and subgroups with diminished ovarian reserve (DOR) or polycystic ovary syndrome (PCOS). Results In the entire participants’ cohort, no correlation between vitamin D deficiency and pregnancy results was observed (p > 0.05). However, in the DOR subgroup, vitamin D deficiency was associated with a lower biochemical pregnancy rate (adjusted OR 0.27; 95% CI 0.08–0.90; p < 0.01) and clinical pregnancy rate (adjusted OR 0.36; 95% CI 0.14–0.90; p < 0.01). No significant differences were observed in pregnancy outcomes among patients with PCOS (p > 0.05). Conclusion Vitamin D deficiency does not affect pregnancy outcomes in the overall patient population, but it may negatively impact women with DOR potentially leading to poorer pregnancy outcomes. Further studies are needed to clarify the mechanisms involved and the potential use of vitamin D screening and supplementation in specific populations.